Coaching Clinic Online: Pembuatan Artikel Ilmiah - Auliana, Rini Adriani; Fitri, Yelli; Fatimah, Siti; Switrayana, I Nyoman; Talidobel, Susilo; Ramdani, Rizal; Solina, Eva (Universitas Mataram, 2025)
This coaching clinic activity aims to improve and provide students with an understanding of the techniques and methods of writing scientific articles, determining research theories and appropriate research methodologies. This coaching clinic is carried out through a participatory approach and learning by doing, as well as with a learning scheme. This coaching clinic activity was conducted online through the MS Teams application platform, with 15 participants from the Accounting Department of Universitas Terbuka who came from regions throughout Indonesia. This activity was carried out four times with each meeting lasting a maximum of 120 minutes. The results of the activity were very significant, seen from the students' ability to write good scientific articles, even some scientific articles written by the training participants are planned to be published in reputable national journals. The impact of this activity was felt not only by the students who participated in the training but also by the supervising lecturers and the university.